Age-hardening in a two component immiscible nanolaminate metal system. (15th July 2017) - Kim, Chang-Eun; Rahimi, Raheleh M.; Maxwell, Tyler L.; Balk, T. John; Bahr, David F.
Abstract: Density functional theory was used to predict the diffusion and precipitation of Cr in Cu. The energy barrier of Cr diffusion in Cu is comparable to the self-diffusion of Cr, and higher than the energy barrier of Cu self-diffusion. The simulations support the experimentally measured hardness of 30 nm thick nanolaminate layers of Cr/Cu-3.4%Cr. As-deposited films had a hardness of 6.25 GPa; annealing at 373 K decreased hardness to 5.95 GPa, while annealing at 573 K increased the hardness to 6.6 GPa. Transmission electron microscopy indicates there is significant local strain due to precipitation, in agreement with theoretical predictions. Graphical abstract: